PENGARUH REWARD, PUNISHMENT DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PT TANI SEJATI MANDIRI MALANGPENGARUH REWARD, PUNISHMENT DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PT TANI SEJATI MANDIRI MALANG - Rindi Anisa Putri, Nava; Nugraha, Alifian (Jurnal PubBis, 2024)
One of the aspects that is important for a corporate organization is employee work productivity. Corporate performance is assessed as good with a high level of productivity, and vice versa if it is assessed as poor with a low level of productivity. Some of the main efforts to achieve optimal work productivity include training and motivation. The aim of this research is to determine the effect of reward, punishment, and motivation on employee work productivity. This is quantitative research with an explanatory (cause-and-effect) approach. The population in this study were all 34 employees of PT Tani Sejati Mandiri Malang. Sampling in this study used a saturated sampling technique. The analytical method used is multiple linear regression with SPSS 26 software. From the overall hypothesis, it shows that reward partially influences employee work productivity, punishment partially influences employee work productivity, and motivation does not partially influence employee work productivity. Reward, punishment, and motivation have a simultaneous influence on employee work productivity. It can be concluded that reward, punishment, and motivation have a significant effect on employee work productivity at PT Tani Sejati Mandiri Malang. An increase in employee work productivity can have an impact on business progress.  Keyword : Reward, Punishment, Motivation, Employee Productivity, Multiple Linear Regressi